Charlie & Mouse Outdoors - Book 4 - Snyder, Laurel; Hughes, Emily (Emily M.) (San Francisco : Chronicle Books, 2020)
Charlie and Mouse and their parents are going on a camping trip, and there will be hiking, storytelling, marshmallows, and campfires, and the joy that comes from sharing it all.
Keywords: Brothers -- Juvenile fiction; Camping -- Juvenile fiction; Families -- Juvenile fiction; Family life -- Juvenile fiction